Muscle growth in Antarctic and Subantarctic notothenioid fishes - Fernández, Damián Andrés; Calvo, Jorge; Johnston, Ian Alistair (Scientia Marina)
The suborder Notothenioidei comprises 122 species divided into 8 families, with members of 6 of the families living outside Antarctic waters. The Antarctic species underwent an extensive radiation from a small demersal ancestor to occupy different ecological niches and levels in the water column. The axial muscle of Antarctic and some Subantarctic notothenioids is unusual in containing very large diameter muscle fibres and a low muscle fibre number. Maximum fibre diameters are greater than 500 μm in many species. There is no indication of systematic differences in fibre number, fibre type composition, ATPase activity, time of cessation of fibre recruitment (hyperplasia) and swimming performance between Antarctic and Subantarctic species. Instead, fibre number is significantly decreased in species belonging to the most derived families relative to the more basal families (a trend that also correlates with an increase in the diameter of the fibres). The length of the cell cycle of the muscle fibres shows cold compensation in the Antarctic species H. antarcticus relative to the closely related Subantarctic one (H. bispinis). Feeding after a starvation period results in a strong stimulation of the proliferation of muscle fiber progenitors in H. bispinis. Similar studies have not yet been performed on any Antarctic species. Fil: Fernández, Damián Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Ohio Wesleyan University.; Estados Unidos Fil: Calvo, Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Johnston, Ian Alistair. University of St. Andrews; Reino Unido